A Cooperative Work Perspective on Use and Development of Computer Artifacts - Sørgaard, Pål (DAIMI Report Series, 1987)
This paper presents a cooperative work perspective on the role of computer artifacts in organisations. Traditionally the issue of cooperative work has been given little attention in the design of computer artifacts, and in fact much cooperative work has been disrupted rather than supported by computers. Cooperative work is seen as a specific, prototypical kind of work with many desirable properties. Cooperative work has an informal nature and often this will not be reflected in the formal organisation of the work, its importance often being neglected. Cooperative work will often be found in health care teams, in office work, in many project groups, and also in many kinds of mechanical work. Two ways of coordinating cooperative work can be identified. Coordination by explicit communication and coordination through the shared material of the working process. In parallel to this there are two main forms of computer support for cooperative work, computerised media for explicit communication and computer implemented shared material.